From EFL to EMI: The evolving English learning motivation of Mainland Chinese students in a Hong Kong University. (August 2018) - Du, Xujia; Jackson, Jane
Abstract: Drawing on self-based L2 motivation theories, the present study explored changes in the English learning motivation of eight Mainland Chinese undergraduates after their arrival at a Hong Kong university, where they took most of their courses in English. The participants were surveyed and interviewed retrospectively about their English learning experiences both in Mainland China and Hong Kong. After their relocation to Hong Kong, most participants reported heightened motivation. While their motivation generally remained stable at a high level, there were some fluctuations. The motivational enhancement may be influenced by the continuous interaction between the participants' perceptions of different contexts of Hong Kong and their shifting actual and ideal L2 selves. The motivational fluctuations appeared to be affected by an interplay between the participants' L2 selves and specific L2-related learning experiences such as preparation for English proficiency tests. As these activities came to an end, the participants' motivation returned to its original state. Implications are offered to support the transitions of English as a foreign language learners to an environment where English is used as the medium of instruction.